Evaluating methods for determining mercury concentrations in ancient marine fish and mammal bones as an approach to assessing millennial-scale fluctuations in marine ecosystems - Avery, Julie P.; Castellini, J. Margaret; Misarti, Nicole; Keenan, Mary; Gastaldi, Angela; Funk, Caroline; O’Hara, Todd M.; Rea, Lorrie D. (Frontiers in Ecology and Evolution, 2023)
Millennial-scale datasets of heavy metals in biota are difficult to obtain but are important for determining patterns and underlying drivers of toxicant concentrations to better discriminate contemporary natural and anthropogenic sources. Globally mercury is a contaminant of concern. As bone is a tissue that is well preserved in archeological middens, it may prove useful for developing longterm mercury data sets under appropriate conditions. The goal of this study was to evaluate methodologies for measuring mercury concentration in bone using a direct mercury analyzer, considering sample preparation methods and variability among bone tissue types (e.g., compact versus spongy bone). Finally, we directly compare sensitivity and precision of two different direct mercury analyzer models. Based on the methods presented here, direct mercury analysis using the Nippon MA-3000 can quantify small (ppb) quantities of Hg accurately and precisely in 20 to 60mg of bone with minimal specimen processing. The described method is efficient, relatively inexpensive, and requires minimal bone, conserving rare and valuable specimens. Differences between compact and spongy bone [THg] exist within some individual specimen; however, the difference is not consistent and may indicate differential Hg exposure windows influenced by turnover rate of bone types. We conclude bone provides a natural archive for mercury ecosystem dynamics over millennial time scales in regions where appropriate samples are available. Comparisons of [THg] between bone type within individual may provide insight into more acute changes in mercury exposure within an individual's lifetime.